About Accuracy of Methods for Numerical Modeling of Heating and Cooling Processes Used for Power Resource Expenditure Optimization - A. N. Chichko; O. A. Sachek (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A numerical analysis of the temperature field which is cooled according to analytical and numerical schemes is given in the paper. The paper shows that an implicit scheme is closer to an analytical solution.